Global research trends in gastroenteropancreatic neuroendocrine tumors: a bibliometric analysis from 2000 to 2023 - Wu, Lei; Wang, Tongfei; Jiang, Siyuan; Zhang, Juan; Zhang, Mi; Gao, Huan; Wang, Hui; Zhou, Yan; Ran, Ran; Dong, Danfeng; Yang, Jin (Frontiers in Oncology, 2025)
IntroductionThe incidence of gastroenteropancreatic neuroendocrine tumors (GEP-NETs) is increasing. To improve patient outcomes, it is essential to develop integrated treatment strategies based on tumor characteristics. Researchers need a rapid visualization of global research trends in GEP-NETs. However, there is currently no bibliometric analysis of GEP-NETs available. This paper aims to fill this gap by using bibliometric methods to quantitatively visualize the current status and research hotspots of GEP-NETs from 2000 to 2023, thereby providing a reference for future research.MethodsWe analyzed 1,140 English publications on GEP-NETs from 2000 to 2023, sourced from the Web of Science Core Collection (WOSCC). Microsoft Excel 2021, CiteSpace, and VOSviewer were used for bibliometric analysis and visualization.ResultsFrom 2000 to 2023, the number of annual publications on GEP-NETs steadily increased. We identified 1,140 articles published in 401 journals by 5,751 authors from 55 countries. The United States emerged as a leading contributor to GEP-NETs research. Erasmus University Rotterdam, the journal Neuroendocrinology, and the author De Herder WW had the highest number of publications. The most frequently cited reference was by Dasari A. A co-word analysis of keywords revealed five research clusters within the field of GEP-NETs. Immunotherapy and peptide receptor radionuclide therapy (PRRT) are prominent research trends. The terms “carcinoid tumors” and “Lu 177 dotatate” showed significant burst strength.ConclusionsWith the rising incidence of GEP-NETs, there is an increasing focus on their diagnosis and treatment. This bibliometric analysis spotlights the current status, key contributors, top journals, influential publications, and the trends of research topics on GEP-NETs. It provides a comprehensive overview of GEP-NETs research from 2000 to 2023. By providing this quantitative analysis, our study aims to guide future research efforts and support the development of more effective diagnosis and treatment strategies, ultimately advancing the field of GEP-NETs. Our study can help researchers understand global research trends and future directions in GEP-NETs.